A suitability visualisation method for flood fusion 3D scene guided by disaster information. (2nd October 2021) - Luo, Lan; Zhu, Jun; Fu, Lin; Pirasteh, Saied; Li, Weilian; Han, Xiao; Guo, Yukun
ABSTRACT: Enhancing the visualisation of floods is essential for users to understand disaster information. However, existing flood visualisation methods have some deficiencies like scarce scene content expression and difficulty obtaining disaster information quickly and lacked a semantic description of the disaster scenes. This study presents constraint rules of flood disaster scene modelling guided by disaster information to determine the disaster's content and correlation. We created a disaster fusion expression model to obtain the complete flood disaster scene which integrated basic geography scene, flood space-time process and disaster object models. Finally, we proposed a dynamic suitability visualisation method for the flood scene to increase the readability of disaster information. We applied the proposed model in the Danba County flood in Sichuan Province, China, to validate the model's performance effectiveness. The finding shows the variation range of flow velocity and flood depth at different monitoring points at a specific time, and also shows the disaster level of disaster objects in the study area. It indicates that the proposed method can effectively realise the fusion of 3D disaster scenes and the dynamic suitability visualisation of floods and help users understand floods quickly and get useful disaster information.